2015
DOI: 10.1080/14615517.2015.1049488
|View full text |Cite
|
Sign up to set email alerts
|

Critical challenges to consultants in pursuing quality of Environmental and Social Impact Assessments (ESIA) in Cambodia

Abstract: The challenges faced by consultants in improving ESIA quality in Cambodia are discussed in this paper. Despite progress since its introduction in 1996, ESIA practice and the role of stakeholders in Cambodia remain inconsistent, resulting in assessment reports that show significant gaps in critical information. Based on interviews, observations and report reviews, the role of the consultant is found to be vital. Certain shortcomings need to be addressed: consultancy roles are legislatively mandated; there is un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…The total number of EIARs was not given. The sample size was decided with reference to past case studies, which showed 112 samples were used in European countries (Wood et al 1996), 72 in Greece (Cashmore et al 2002), 50 in Estonia (Peterson 2010), 46 in Portugal and Spain (Canelas et al 2005), 45 in Egypt (Badr et al 2011), 39 in Cambodia (Chanthy & Grünbühel 2015), 30 in Bangladesh (Momtaz & Kabir 2013), and 28 in South Africa (Sandham & Pretorius 2008). The sample size exceeded the largest size of any previous study and was judged sufficient for the study.…”
Section: Selection Of Samplementioning
confidence: 99%
See 1 more Smart Citation
“…The total number of EIARs was not given. The sample size was decided with reference to past case studies, which showed 112 samples were used in European countries (Wood et al 1996), 72 in Greece (Cashmore et al 2002), 50 in Estonia (Peterson 2010), 46 in Portugal and Spain (Canelas et al 2005), 45 in Egypt (Badr et al 2011), 39 in Cambodia (Chanthy & Grünbühel 2015), 30 in Bangladesh (Momtaz & Kabir 2013), and 28 in South Africa (Sandham & Pretorius 2008). The sample size exceeded the largest size of any previous study and was judged sufficient for the study.…”
Section: Selection Of Samplementioning
confidence: 99%
“…2008; Badr et al 2011;Momtaz & Kabir 2013;Sandham et al 2013;and Chanthy & Grünbühel 2015). Previous studies used the summary tables to illustrate grades and the portion of grades that were satisfactory and unsatisfactory, and then went on to discuss the improvement in quality.…”
Section: Introductionmentioning
confidence: 99%
“…The EIA process in Cambodia was established with the Law on Environmental Protection and Natural Resource Management, 1996 (Swangjang 2018). In 1999, a sub-decree was developed regarding environmental and social impact assessment (Chanthy and Grünbühel 2015). While these laws remain in place, environmental law in Cambodia has been under review since 2012.…”
Section: Cambodiamentioning
confidence: 99%
“…Problems have been identified with this process, as the consulting firms are potentially affected by political influence and local elites, and they generally lack expertise, time, access to data, and financing (Chanthy and Grünbühel 2015).…”
Section: Cambodiamentioning
confidence: 99%
“…Conducting an assessment requires teamwork and the collaboration of its members, the technical aspects alone do not determine the success or failure of Environmental and Social Impact Assessment (ESIA) performance [26]. Depending on the complexity of the project, sub-contracting of additional experts may be needed for full coverage of all technical aspects, and harmonization among various technical and management specialists is a must [25].…”
Section: Authorization and Certification Of The Experts Or Firms Of Ementioning
confidence: 99%